Percepção docente acerca da motricidade infantil em uma creche em Concórdia-PA - LIMA, Gleice Nunes de (2019)
The present study aimed to present the main contributions of motor skills regarding child development in the Municipal School of Nursing Teacher Rubeni de Souza Lima in Concórdia - PA. In order to understand how motor skills can contribute to the integral formation of children, more precisely in early childhood education. Reflecting on body movement in school everyday and how the body, through movement is treated in this teaching / learning action at this school stage. Identify the actions of the teachers involving the corporal movement in the educational action, and if they work the motricidade with ludic activities, aiming the teaching / learning, with the purpose to evolve, to balance, to teach and to raise the interest to learn of its educando. The study was developed using as main investigated three teachers of the Infantile Education in the classes of Garden I and II of Infantile Education, both acting in the abovementioned school. Bibliographic research, interviews, and five in situ observations were carried out. It is concluded that motor skills are an indispensable and important tool in the integral formation of children in early childhood education. However, in the school investigated, the infrastructure, together with the lack of better preparation of some teachers, showed the inefficient development of activities with motor skills. an urgent need to acquire more materials and training to work on motor activities.